Patterns of failure in pediatric medulloblastoma and implications for hippocampal sparing. Issue 5 (11th December 2022) - Baliga, Sujith; Adams, Judith A.; Bajaj, Benjamin V. M.; Van Benthuysen, Liam; Daartz, Juliane; Gallotto, Sara L.; Lewy, Jacqueline R.; DeNunzio, Nicholas; Weyman, Elizabeth A.; Lawell, Miranda P.; Palmer, Joshua D.; Yeap, Beow Y.; et al.
Abstract: Background: Hippocampal avoidance (HA) has been shown to preserve cognitive function in adult patients with cancer treated with whole‐brain radiation therapy for brain metastases. However, the feasibility of HA in pediatric patients with brain tumors has not been explored because of concerns of increased risk of relapse in the peri‐hippocampal region. Our aim was to determine patterns of recurrence and incidence of peri‐hippocampal relapse in pediatric patients with medulloblastoma (MB). Methods and materials: We identified pediatric patients with MB treated with protons between 2002 and 2016 and who had recurrent disease. To estimate the risk of peri‐hippocampal recurrence, three hippocampal zones (HZs) were delineated corresponding to ≤5 mm (HZ‐1), 6 to 10 mm (HZ‐2), and >10 mm (HZ‐3) distance of the recurrence from the contoured hippocampi. To determine the feasibility of HA, three standard‐risk patients with MB were planned using either volumetric‐modulated arc therapy (VMAT) or intensity‐modulated proton therapy (IMPT) plans. Results: Thirty‐eight patients developed a recurrence at a median of 1.6 years. Of the 25 patients who had magnetic resonance imaging of the recurrence, no patients failed within the hippocampus and only two patients failed within HZ‐1. The crude incidence of peri‐hippocampal failure was 8%. Both HA‐VMAT and HA‐IMPT plans were associated with significantly reduced mean dose to the hippocampi ( p < .05). HA‐VMAT and HA‐IMPT plans were associated with decreased percentage of the third and lateral ventricles receiving the prescription craniospinal dose of 23.4 Gy. Conclusions: Peri‐hippocampal failures are uncommon in pediatric patients with MB. Hippocampal avoidance should be evaluated in a prospective cohort of pediatric patients with MB. Plain Language Summary: In this study, the patterns of disease recurrence in patients with a pediatric brain tumor known as medulloblastoma treated with proton radiotherapy were examined. The majority of failures occur outside of an important structure related to memory formation called the hippocampus. Hippocampal sparing radiation plans using proton radiotherapy were generated and showed that dose to the hippocampus was able to be significantly reduced. The study provides the rationale to explore hippocampal sparing in pediatric medulloblastoma in a prospective clinical trial. Abstract : The incidence of peri‐hippocampal failures in patients treated with proton radiotherapy for pediatric medulloblastoma was 8%. Hippocampal sparing plans were associated with significant reduction in the mean dose to the right and left hippocampi.